IELTS Academic 19 with Answers : authentic practice tests with audio (Cambridge: New York: Cambridge University Press, 2024)
Inside IELTS 19 Academic with Answers with Audio with Resource Bank you'll find FOUR complete examination papers plus details of the different parts of the test and the scoring system, so you can familiarize yourself with the Academic test format and practice your exam technique. Download the audio for the Listening tests, example Speaking test videos, answer keys with extra explanations and sample Writing answers (instructions on inner front cover), or access your audio and video directly via QR codes in the book.
Test 1 -- Test 2 -- Test 3 -- Test 4 -- Audioscripts -- Listening and reading answer keys -- Sample writing answers -- Sample answer sheets.
With resource bank.
Keywords: International English Language Testing System -- Study guides; English Language -- Examinations, Question; English language -- Textbooks for foreign speakers